2015
DOI: 10.1111/bij.12453
|View full text |Cite
|
Sign up to set email alerts
|

Independent origins of the feather lice (Insecta:Degeeriella) of raptors

Abstract: Although diurnal birds of prey have historically been placed in a single order due to a number of morphological characters, recent molecular phylogenies have suggested that this is a case of convergence rather than homology, with hawks (Accipitridae) and falcons (Falconidae) forming two distantly related groups within birds. The feather lice of birds have often been used as a model for comparing host and parasite phylogenies, and in some cases there is significant congruence between the two. Thus, studying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Individuals in the QUAD‐M and QUAD‐S clades both seem to be able to infect multiple members of the T. quadrivittatus host species group and the structure among these pinworms appears to be primarily geographic, as has been demonstrated in other parasite taxa (Catanach & Johnson, ). Furthermore, all the QUAD‐N and QUAD‐M localities and several of the QUAD‐S localities are found within the geographic distribution of T. minimus , yet we only captured one instance of a switch to a T. minimus host in the QUAD clades.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in the QUAD‐M and QUAD‐S clades both seem to be able to infect multiple members of the T. quadrivittatus host species group and the structure among these pinworms appears to be primarily geographic, as has been demonstrated in other parasite taxa (Catanach & Johnson, ). Furthermore, all the QUAD‐N and QUAD‐M localities and several of the QUAD‐S localities are found within the geographic distribution of T. minimus , yet we only captured one instance of a switch to a T. minimus host in the QUAD clades.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve host species of Colpocephalum included in this phylogenetic study also harbour Degeeriella , a second louse genus parasitizing diurnal birds of prey. These Degeeriella species were previously included in a phylogenetic study of the genus (Catanach & Johnson, ). Following the methods outlined in Sweet, Boyd, and Johnson (), we used the R implementation of PARAFIT (in package “ape”; Legendre, Desdevises, & Bazin, ; Paradis, Claude, & Strimmer, ) to evaluate whether cophylogenetic patterns were correlated between the two codistributed louse genera.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, molecular phylogenetic data have called into question the validity of many louse genera that parasitize distantly related hosts. For example, the ischnoceran louse genus Degeeriella Neumann, 1906, which parasitizes hawks (Accipitriformes) and falcons (Falconiformes), consists of two distinct, distantly related non‐sister lineages, one specific to each host order (Catanach & Johnson, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All other Chloroceryle americana lice included in our phylogeny are from South America and identified as Alcedoffula columbiana Carriker, 1959. This paraphyly among Chloroceryle americana lice could be the result of geographically specific louse species infecting a single host species (Catanach and Johnson, 2015). Catanach and Johnson (2015) found that Old World and New World Buteo lagopus Pontoppidan, 1763 (Accipitriformes, Accipitridae) were parasitized by distantly related lice.…”
Section: Parasitology 1089mentioning
confidence: 99%